Islamic Economic Principles Review of Cooperative Practices in Broiler Chicken Farming in Geragai District - Suparno; Wargo (Zabags Qu Publish, 2025)
This study examines cooperative practices in broiler chicken farming in Geragai District, where the prevalent core–plasma partnership model raises persistent issues of equity, transparency, and risk distribution. The primary objective is to describe the cooperation between plasma farmers and core companies and assess its alignment with Islamic economic principles. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis, and were subjected to thematic analysis with triangulation to ensure validity. Findings indicate that core companies dominate price setting, chick quality, and harvest timing, while plasma farmers bear mortality risk and additional costs, producing an uneven allocation of profits and risks. Contracts are frequently insufficiently detailed or not fully documented in writing, resulting in ambiguous agreements that contravene Islamic commercial ethics. The study contributes theoretically by reaffirming the relevance of the concepts of syirkah and mudharabah in evaluating partnership models, and practically by recommending more equitable, transparent, and Sharia-compliant contracts. It also highlights implications for future research and the need to strengthen Sharia legal literacy among plasma farmers.